Facile controlled synthesis of coral-like nanostructured Sb2O3@Sb anode materials for high performance sodium-ion batteries. (20th March 2020) - Ye, Jiajia; Xia, Guang; Zheng, Zhiqiang; Hu, Cheng
Abstract: Sb2 O3 @Sb composites consisting of a coral-like nano-Sb skeleton with surface decorated Sb2 O3 nanoparticles were synthesized and evaluated as sodium-ion battery anodes. The facile synthesis route involves etching of elemental Al from a Sb5 Al95 alloy to obtain the coral-like nano-Sb, which was then subjected to mild oxidization in air to introduce Sb2 O3 . The optimal elemental and phase composition was achieved by tuning and controlling the preparation parameters. The Sb2 O3 on the surface synergistically reduces anode volume changes to stabilize the composite structure whilst significantly accelerates the electrochemical kinetics. The three-dimensional network in Sb2 O3 @Sb composite also possesses a uniform porous structure that effectively relieves the volume changes and provides fast Na + transportation channels. The best Sb2 O3 @Sb composite from this study shows the significantly improved specific capacity of 724.3 mAh g −1 at 1000 mA g −1 current density, with 526.2 mAh g −1 of specific capacity remained after 150 charge-discharge cycles. A high specific capacity of 497.3 mAh g −1 was achieved at 3000 mA g −1, which to our knowledge performs the best among most Sb-based anodes reported in the literature. This on top of its facile synthesis makes the Sb2 O3 @Sb composite a viable anode candidate for future sodium-ion batteries. Highlights: Coral-like nano-Sb decorated with Sb2 O3 nanoparticles are prepared as SIB anodes. The coral-like nanostructures interconnect to form an intrinsic 3D porous network. Preparation of the Sb2 O3 @Sb composites is facile but highly controllable. Rating capability of the Sb2 O3 @Sb composite exceeds most existing Sb-based anodes. Specific capacity of 497.3 mAh g −1 at 3000 mA g −1 is achieved.